2020
DOI: 10.1186/s12954-020-00397-w
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis health knowledge and risk perceptions among Canadian youth and young adults

Abstract: Background: Although recreational cannabis is now legal in Canada, little empirical evidence exists regarding young Canadians' cannabis literacy, cannabis-related risk perceptions, and risk of different forms of cannabis or the effect that public health education may have on these perceptions. The present study sought to address these knowledge gaps to examine health knowledge and risk perceptions associated with cannabis use. Methods: An online survey was conducted with a national sample (N = 870) of Canadian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…While participants in our study suggested the need for an increase in school-based educational initiatives to assist in normalizing conversations and educating youth about the harms associated with use, they also suggested the utility of social media-based campaigns as a means to provide information to help shift the discourse and reduce the stigmatizing attitudes towards use. A recent national survey of Canadians aged 16 to 30 years found that while viewing advertisements and educational messages about cannabis was uncommon (less than one-third of participants reported seeing messages about cannabis in the past year), digital media was the most common place for encountering public health messages regarding cannabis use [ 34 ]. This suggests a need for expansion of education-based prevention programs through various channels including digital and television media in addition to schools to ensure it reaches the targeted youth population.…”
Section: Discussionmentioning
confidence: 99%
“…While participants in our study suggested the need for an increase in school-based educational initiatives to assist in normalizing conversations and educating youth about the harms associated with use, they also suggested the utility of social media-based campaigns as a means to provide information to help shift the discourse and reduce the stigmatizing attitudes towards use. A recent national survey of Canadians aged 16 to 30 years found that while viewing advertisements and educational messages about cannabis was uncommon (less than one-third of participants reported seeing messages about cannabis in the past year), digital media was the most common place for encountering public health messages regarding cannabis use [ 34 ]. This suggests a need for expansion of education-based prevention programs through various channels including digital and television media in addition to schools to ensure it reaches the targeted youth population.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies reported on youth and young adults’ harm perceptions of cannabis vaping [ 176 , 177 , 181 , 191 ]. One study reported that young adults perceived combustible (e.g., smoked, via a joint or pipe) cannabis as more harmful than vaporized cannabis; however, chemicals (e.g., butane) used make cannabis concentrates were thought to be a source of harm [ 181 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies also reported uncertainty about the safety and harms of cannabis vaping compared to other forms of use [ 177 , 191 ]. One study reported that youth and young adult cannabis vapers had lower odds of perceiving harm from daily cannabis use in any form, when compared to never cannabis users [ 176 ]. Risk factors and reasons for use associated with cannabis vaping among youth and young adults are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…However, this finding is not self-evident as literature has shown that the general public, particularly cannabis users, do not perceive cannabis use as harmful. In addition, within the public discourse, there is the perception that cannabis use has few negative consequences on health (Gali et al, 2021;Leos-Toro et al, 2020). For example, Leos-Toro et al (2020) reported that never and ever users were more likely to report cannabis-related physical concerns than current users (AOR = 1.89, 95% CI [1.26,2.85], p = 0.002; AOR = 1.57, 95% CI [1.07,2.31], p = 0.002, respectively).…”
Section: Explanation Of Findingsmentioning
confidence: 99%
“…In addition, within the public discourse, there is the perception that cannabis use has few negative consequences on health (Gali et al, 2021;Leos-Toro et al, 2020). For example, Leos-Toro et al (2020) reported that never and ever users were more likely to report cannabis-related physical concerns than current users (AOR = 1.89, 95% CI [1.26,2.85], p = 0.002; AOR = 1.57, 95% CI [1.07,2.31], p = 0.002, respectively). In addition, the study found that ever and current users were less likely to report that using cannabis may harm their mental health compared to never users (AOR = 0.48, 95% CI [0.31,0.74], p = 0.001; AOR = 0.35, 95% CI [0.22,0.56], p <0.001, respectively).…”
Section: Explanation Of Findingsmentioning
confidence: 99%